Prevalence of Xenopsylla cheopis in Rattus rattus in the Salas district, Lambayeque: Prevalencia de Xenopsylla cheopis en Rattus rattus en el distrito de Salas, Lambayeque - Ortiz-Cusma, Jarling F. (2022)
Objective: The study of the prevalence of Xenopsylla cheopis in rodents of the Rattus rattus species.The objective of the present investigation is to establish the prevalence of Xenopsylla cheopis in rodents of the Rattus rattus species. Methods: To obtain the sample, Tomahawk and Sherman traps were used that contained baits previously prepared with oatmeal and vanilla, the traps were placed in three areas: intra-home area, peridomyciliary area and in the open area. Ectoparasites were obtained using the fine comb technique. With an entomological clamp, fleas were collected in a 2ml vial, containing 70% alcohol. Results: Its prevalence in Rattus rattus rodents were evaluated, with the highest prevalence rate being the one registered in the locality of Banco in August 2016 (4.08) and the lowest index was 1.3 registered in the locality of the Ramada in November 2015. They were captured 169 rodents Rattus rattus, of which 399 fleas could be collected, 299 belonged to the Xenopsylla cheopis species. Conclusion: it was found that the prevalence of Xenopsylla cheopis in Rattus rattus rodents in the locations of Sauce, Banco, Kerguer, Algarrobo, and Ramada in the Salas district, in the period July - November 2015 and August 2016 was high.